1995
DOI: 10.1161/01.res.77.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Activates pp60 c- src in Vascular Smooth Muscle Cells

Abstract: The angiotensin II type-1 (AT1) receptor, a G protein-coupled receptor, lacks intrinsic kinase activity. However, recent data show that angiotensin II (Ang II) stimulates tyrosine phosphorylation of phospholipase C-gamma 1 (PLC-gamma 1), Stat91 (one of the signal transducers and activators of transcription), and paxillin in vascular smooth muscle cells. The tyrosine kinases responsible for these phosphorylation events are unknown. Src family kinases have been shown to phosphorylate PLC-gamma 1 and to be activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 34 publications
4
104
1
Order By: Relevance
“…Early experiments demonstrated that Src, Fyn or Yes could be activated by a host of GPCRs, including the lysophosphatidic acid (LPA), a2A adrenergic, M1 muscarinic, M2 muscarinic, a-thrombin, endothelin, angiotensin II, bombesin, bradykinin, and V2 vasopressin receptors (Simonson and Herman, 1993;Chen et al, 1994;Ishida et al, 1995;Kramer et al, 1995;Linseman et al, 1995;Ptasznik et al, 1995;Luttrell et al, 1996;Rodriguez-Fernandez and Rozengurt, 1996;Schieffer et al, 1996;Simonson et al, 1996). From the outset, there was evidence for heterogeneity in the mechanisms underlying GPCR control of Src activity.…”
Section: Gpcr Activation Of Src Family Kinases: When Worlds Collidementioning
confidence: 99%
“…Early experiments demonstrated that Src, Fyn or Yes could be activated by a host of GPCRs, including the lysophosphatidic acid (LPA), a2A adrenergic, M1 muscarinic, M2 muscarinic, a-thrombin, endothelin, angiotensin II, bombesin, bradykinin, and V2 vasopressin receptors (Simonson and Herman, 1993;Chen et al, 1994;Ishida et al, 1995;Kramer et al, 1995;Linseman et al, 1995;Ptasznik et al, 1995;Luttrell et al, 1996;Rodriguez-Fernandez and Rozengurt, 1996;Schieffer et al, 1996;Simonson et al, 1996). From the outset, there was evidence for heterogeneity in the mechanisms underlying GPCR control of Src activity.…”
Section: Gpcr Activation Of Src Family Kinases: When Worlds Collidementioning
confidence: 99%
“…Activation of PLC␥ requires tyrosine phosphorylation as shown by inhibition of Ins(1,4,5)P 3 formation with inhibitors such as herbimycin A and genistein (13). A specific role for Src was suggested by demonstrating rapid activation of Src in VSMC, inhibition of PLC␥ activation with antibodies to Src, and impaired signal transduction in SrcϪ/Ϫ cells (12,16,23). It is well known that PLC␥1 and PLC␥2 are substrates for members of the Src kinase family (24,25).…”
mentioning
confidence: 99%
“…56,57 In smooth-muscle cells it has been shown that, for this purpose, the AT 1 receptor has to recruit the soluble tyrosine kinase pp60 c-src , since the receptor itself lacks intrinsic kinase activity. 58 PLC-g1 phosphorylation leads to the PIP 2 hydrolysis into 1,4,5-IP 3 and diacylglycerol. The induction of 1,4,5-IP 3 leads to intracellular calcium release, which in turn induces smooth-muscle cell contraction and other signaling events.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 99%